Bleeding control during laparoscopic liver resection: a review of literature. (22nd January 2015) - Tranchart, Hadrien; O'Rourke, Nicholas; Van Dam, Ronald; Gaillard, Martin; Lainas, Panagiotis; Sugioka, Atsushi; Wakabayashi, Go; Dagher, Ibrahim
Abstract: Despite the established advantages of laparoscopy, bleeding control during laparoscopic liver resection (LLR) is a liver‐specific improvement. The 2nd International Consensus Conference on Laparoscopic Liver Resection was held in October 2014 at Morioka, Japan. One of the most capital questions was: What is essential in bleeding control during LLR? In order to correctly address this question, we conducted a comprehensive review of the literature. Essential points based on personal experience of the expert panel are also discussed. A total of 54 publications were identified. Based on this analysis, the working group built these recommendations: (1) a pneumoperitoneum of 10–14 mmHg should be used as it allows a good control of the bleeding without significant modifications of hemodynamics; (2) a low central venous pressure (<5 mmHg) should be used; (3) laparoscopy facilitates inflow and outflow control; and (4) surgeons should be experienced with the use of all surgical devices for liver transection and should master laparoscopic suture before starting LLR. Precoagulation with radiofrequency can be useful, particularly in cases of atypical resection. These recommendations are mostly based on experts' opinions and on B or C quality of evidence grade studies. More prospective data are required to confirm these results.